A critical analysis of modification effects on nanostructured TiO2-based photocatalysts for hydrogen production - Ayodele, Bamidele Victor; Siti Indati, Mustapa; Alsaffar, May Ali; Vo, Dai Viet N.; Sureena, Abdullah (Elsevier, 2021)
Photocatalytic reforming of hydrocarbon is a promising alternative for producing renewable hydrogen. Compared with the conventional thermochemical processes used for hydrogen production, photocatalytic reforming offers the advantages of using the vast abundance of solar energy resources and the affordable, nontoxic photocatalysts for hydrogen production. Besides, the constraints of catalyst deactivations and the high thermal energy required for steam production are avoided in the photocatalytic reforming processes. Titanium dioxide (TiO2), a readily available photocatalyst, has gained wide acceptance as a photocatalytic materials used for hydrogen production because of its excellent physicochemical properties. The modification of the TiO2 nanostructure with various dopants or cocatalysts has been proven to improve its properties and enhance the rate of hydrogen production. This chapter presents the analysis of selected literature on the modification effect on nanostructure TiO2-based photocatalysts used for hydrogen production. Noble metals such as platinum (Pt) and ruthenium (Ru) were found to significantly enhance the photocatalytic activity of TiO2 nanostructure. Besides, nonnoble metals such as Ni and Cu used as dopants or cocatalysts were also found to influence the properties of TiO2 during photocatalytic hydrogen production. The mechanisms of the photocatalytic hydrogen production are strongly dependent on the nature of the photocatalysts as well as the sacrificing agent used.